Effects of biofuels properties on aircraft engine performance - Mazlan, Nurul Musfirah; Savill, Mark A.; Kipouros, Timoleon (Emerald, 2015)
Purpose-The purpose of this paper is to examine the effects of heat capacity and density of biofuels on aircraft engine performance indicated by thrust and fuel consumption. Design/methodology/approach-The influence of heat capacity and density was examined by simulating biofuels in a two-spool high-bypass turbofan engine running at cruise condition using a Cranfield in-house engine performance computer tool (PYTHIA). The effect of heat capacity and density on engine performance was evaluated through a comparison between kerosene and biofuels. Two types of biofuels were considered: Jatropha Bio-synthetic Paraffinic Kerosene (JSPK) and Camelina Bio-synthetic Paraffinic Kerosene (CSPK). Findings-Results show an increase in engine thrust and a reduction in fuel consumption as the percentage of biofuel in the kerosene/biofuel mixture increases. Besides a low heating value, an effect of heat capacity on increasing engine thrust and an effect of density on reducing engine fuel consumption are observed. Practical implications-The utilisation of biofuel in aircraft engines may result in reducing over-dependency on crude oil. Originality/value-This paper observes secondary factors (heat capacity and density) that may influence aircraft engine performance which should be taken into consideration when selecting new fuel for new engine designs.
Keywords: Biofuels; Density; Heat capacity; Aircraft engine performance; Fuel consumption; Thrust